1416 Safety considerations for remediation workers after disasters with indoor water damage, dampness and bioaerosols. (24th April 2018) - Johanning, E; Auger, P; Viegas, S; Viegas, C
Abstract : Introduction: Adverse health outcomes from bioaerosols encountered during the clean-up of indoor environments after disasters or flooding resulting in fungal growth and bio-contamination have been documented. The naive cleaning and restoration of salvaged buildings, furniture and personal items may result in skin contact and inhalation exposure to a mixture of biological compounds with infectious, allergenic, irritant or toxic properties (i.e., mycotoxins). Methods: Review of current safety practices and recommendations by governmental and professional organisations for hygiene and personal protective equipment (PPE) of remediation workers in North America and Europe. Results: A consensus exists that acceptable and safe threshold limits for fungal and bacterial indoor exposure cannot be established. It is generally recommended to control indoor bioaerosol exposures. The route of exposure and target organs of the biological agents may differ (infectious, allergic or toxic effects), is often complex and unpredictable. To capture fungal metabolites (mycotoxins) filters with small pore sizes, namely 0.2 µm are needed. Nevertheless, US governmental agencies focus on a recommendation of N-95 disposable respirator, for respiratory protection, besides gloves and eye protection, but no specific PPE is required. The adequacy, effectiveness and protective level of such a respirator has been questioned. In Canada, clean-up guidelines exist but are not mandated. In Germany, comprehensive rules exist and technical provisions for dust control and PPE are mandated. In Portugal no technical recommendations regarding the type of PPE exist. The medical fitness and surveillance of remediation workers has not been further addressed in any of the guidelines, although this would be prudent based on the pathological profile of bioaerosols. Conclusion: The release of bioaerosols should be controlled with proper containment similar to asbestos remediation projects. The goal of any PPE should be to protect from any contact to the bioaerosols. Medical fitness and monitoring for large scale projects would be prudent.